Perceptions, impacts and rewards of row planting of teff - Vandercasteelen, Joachim; Dereje, Mekdim; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2014)
This study analyzes the perceptions, impacts, and rewards of farmers who adopted row planting for the production of teff as a result of being exposed to a technology promotion campaign for row planting of teff in the Oromia region of Ethiopia.